Rantai Pasok Usaha Penggilingan Padi Studi Kasus : Ud. Putra Tunggal Kabupaten Kolaka Timur - Yuli Purbaningsih; Bahari Bahari; Sitti Aida Adha Taridala; Idrus Salam (Fakultas Pertanian, Universitas Timor, 2021)
This study aims to identify and describe the supply chain system in the rice milling business. This study is an explanatory research. The case study was conducted at UD. Only Son in East Kolaka. The results of this study are, the supply chain system in the rice milling business consists of 2 groups, namely the raw material supply channel (grain) and the product distribution channel (rice). The channel for supplying raw materials (grain) is dominated by the Farmer - Grain Collector - Company channel which has a 50% share of the total annual purchase volume. Meanwhile, the product distribution channel (rice) is dominated by the Company - Wholesaler channel which has a 55% share of the total annual sales volume. The complexity of the supply chain creates the possibility of potential financial risks. Most of the supply chain in terms of volume and percentage (>50%) is traversed by products, namely from farmers, grain traders, UD Putra Tunggal, and wholesalers.